A False Powder-post Beetle, Xylopsocus capucinus (Fabridius) (Insecta: Coleoptera: Bostrichidae) - Robert E. Woodruff; E. J. Gerberg; T. J. Spilman (EDIS)
Xylopsocus capucinus (Fabricius) has previously been intercepted at ports of entry into the U.S. on many occasions in a wide variety of plant materials. However, Fisher (1950) stated that it "has not become established in the United States." On 14 March 1978, specimens were collected from cassava branches at Homestead, Florida, by J. Peña, and subsequent surveys indicate that the species is definitely established as a part of the Florida fauna. This document is EENY-179 (originally published as DPI Entomology Circular 195), one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 2000.